Conceptual Model of Leadership Style, Work Environment and Compensation on Job Satisfaction and Teacher Performance - Nyoto; Sudarno; Sriadmitum, Ike; Renaldo, Nicholas; Hutahuruk, Marice Br (First Ciera Publisher, 2023)
This study aims to analyze the determination of the leadership style of the work environment and compensation on job satisfaction and performance of public high school teachers in Tandun and Ujung Batu sub-districts. The motivation for this research is to form a research model in the field of education, especially teacher satisfaction and performance. This research is quantitative research by distributing questionnaires to respondents. The population in this study were all public high school teachers in Tandun and Ujung Batu sub-districts. The sample selection technique uses the census method. The sample in this study amounted to 90 respondents. Data analysis techniques use the Smart PLS application. The conclusion of this study is that the conceptual model can be used to test the model of job satisfaction and teacher performance. Recommendations for subsequent research are to use the conceptual model that has been made and test the hypothesis on current research objects and other research objects.